Which Method to Use for Surgical Ablation of Atrial Fibrillation Performed Concomitantly with Mitral Valve Surgery: Radiofrequency Ablation versus Cryoablation - Vural,Ünsal (2018)
Abstract Objective: The effects of energy source on the maintenance of sinus rhythm and the contribution of demographic characteristics to the case selection in patients submitted to ablation performed concurrently with mitral valve surgery were analyzed. Methods: Cryothermal (n=42; 43.8%) and radiofrequency (n=54; 56.3%) energy were employed in 96 patients submitted to mitral valve replacement and Cox maze IV procedure. Patients were called for control visits between 15 days and 12 months after discharge. The causal relationship between recurrence of atrial fibrillation and factors such as left atrial diameter, C-reactive protein, hypertension, left ventricular ejection fraction, chronic obstructive pulmonary disease, and body mass index was determined. Results: Maintenance rates of the sinus rhythm with radiofrequency and cryoablation were 97.6% and 96.3%, respectively, in the first postoperative month, whereas at the 12th postoperative month were 88.1% and 83.3%. No significant difference was found between groups in relation to the energy source. Sensitivity and specificity for left atrial diameter with a cut-off value of 50.5 mm were 85.7% and 70.7%, respectively. Sensitivity and specificity for C-reactive protein with a cut-off value of 12 mg/dL on the 15th postoperative day were 83.3% and 88.9%, respectively. The effect of body mass index on atrial fibrillation recurrence was 3.2 times. Sensitivity and specificity for left ventricular ejection fraction 37% cut-off value were 96.3% and 11.4%, respectively. Atrial fibrillation in hypertensive cases was 5.3 times more. In patients with chronic obstructive pulmonary disease, recurrence of atrial fibrillation was 40%. The causal relation between recurrence of atrial fibrillation and the studied factors was established. Conclusion: Demographic characteristics have a significant impact on ablation efficiency, while the type of energy source does not.